2008
DOI: 10.1152/jn.90607.2008
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Selective Attention Modulates Activation of Human Inferior Colliculus

Abstract: Rinne T, Balk MH, Koistinen S, Autti T, Alho K, Sams M. Auditory selective attention modulates activation of human inferior colliculus. J Neurophysiol 100: 3323-3327, 2008. First published October 15, 2008 doi:10.1152/jn.90607.2008. Selective auditory attention powerfully modulates neural activity in the human auditory cortex (AC). In contrast, the role of attention in subcortical auditory processing is not well established. Here, we used functional MRI (fMRI) to examine activation of the human inferior colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 33 publications
(42 reference statements)
7
68
1
Order By: Relevance
“…In other words, the elevations in sound-evoked cortical activation that occurred with tinnitus irrespective of SLT might not reflect the tinnitus percept per se but rather reflect attention drawn to the auditory domain by the presence of tinnitus. The absence of tinnitusrelated effects in subcortical centers in our data is consistent with this attention-based hypothesis for the tinnitus-related effects in PAC because attentional state has a far subtler effect on subcortical compared with cortical auditory fMRI activation (Rinne et al 2008).…”
Section: Dependence Of Pac Activation On Tinnitus: Possible Role Of Asupporting
confidence: 90%
“…In other words, the elevations in sound-evoked cortical activation that occurred with tinnitus irrespective of SLT might not reflect the tinnitus percept per se but rather reflect attention drawn to the auditory domain by the presence of tinnitus. The absence of tinnitusrelated effects in subcortical centers in our data is consistent with this attention-based hypothesis for the tinnitus-related effects in PAC because attentional state has a far subtler effect on subcortical compared with cortical auditory fMRI activation (Rinne et al 2008).…”
Section: Dependence Of Pac Activation On Tinnitus: Possible Role Of Asupporting
confidence: 90%
“…Unilaterally presented sounds are known to induce a significant bilateral fMRI response in human auditory cortex . However modestly, we did observe spatial attention effects in A1 and R; and previous studies have shown spatially-driven attentional modulation in auditory cortex (Rinne et al, 2008. It is possible that spatial attentional modulation would be greater with a task that required more use of spatial information.…”
Section: Discussionsupporting
confidence: 45%
“…Previous human studies suggest that attention modulates responses in the region of primary auditory cortex (EEG: Hillyard et al, 1973;Woods et al, 1984;Woldorff et al, 1993;MEG: Fujiwara et al, 1998fMRI: Jäncke et al, 1999Rinne et al, 2008;EcoG: Bidet-Caulet et al, 2007) including frequency-specific enhancement (Paltoglou et al, 2009;Oh et al, 2012). Other fMRI studies suggest that attentional modulation occurs predominantly in secondary, and not primary, auditory cortical areas (Petkov et al, 2004;Woods et al, 2009;Woods et al, 2010;Ahveninen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous functional magnetic resonance imaging (fMRI) studies have shown that activations of human AC are strongly modulated by attention-engaging auditory tasks (Woodruff et al, 1996;Jäncke et al, 1999;Janata et al, 2002;Rinne et al, 2005;Degerman et al, 2006;Rinne et al, 2008;Mayer et al, 2009). The most pronounced attention-related modulations are typically seen in nonprimary parts of AC in the lateral superior temporal gyrus (STG) (Hall et al, 2000;Petkov et al, 2004;Woods et al, 2009).…”
Section: Introductionmentioning
confidence: 99%